Modern advancements of energy storage systems integrated with hybrid renewable energy sources for water pumping application - Marwa M. Ahmed; Haneen M. Bawayan; Mohamed A. Enany; Mahmoud M. Elymany; Ahmed A. Shaier (Engineering Science and Technology, an International Journal)
This manuscript provides a comprehensive review of hybrid renewable energy water pumping systems (HREWPS), which integrate renewable energy sources such as photovoltaic (PV) systems and wind turbines (WTs) with water pumping technologies to offer sustainable and efficient solutions for water supply in remote and off-grid areas. The study explores the technical and operational aspects of HREWPS, including components, system configurations, energy storage integration, and control methodologies. Basic areas discussed include photovoltaic water pumping systems (PVWPS), with a focus on solar cell technologies, DC-DC converters, motor-pump configurations, and maximum power point tracking (MPPT) techniques; wind energy water pumping systems (WEWPS), analyzing wind turbine designs, motor-pump compatibility, and hybrid configurations; and energy storage systems (ESSs), covering battery technologies, water tanks, and hybrid storage solutions to enhance reliability and mitigate renewable energy intermittency. The manuscript also highlights the integration of artificial intelligence (AI) to optimize energy management, predict irrigation demands, and improve operational efficiency. Additionally, recent advancements in energy storage, such as hybrid configurations of batteries and supercapacitors, are discussed in the context of enhancing system sustainability and reducing operational costs. Case studies from diverse geographical locations demonstrate the economic and environmental benefits of HREWPS, including significant reductions in greenhouse gas emissions and increased agricultural productivity. Despite their potential, challenges such as renewable energy intermittency, optimal sizing, and cost-effectiveness are addressed. The study concludes by identifying gaps in existing research and proposing future directions, such as integrating hydrogen generation, advanced AI algorithms, and innovative energy storage techniques to further enhance the feasibility and impact of HREWPS.